PENGARUH KEPEMIMPINAN DAN BUDAYA KERJA TERHADAP KINERJA KARYAWAN PADA PT DENSHA INDOGUNA JAYA - Sofyandi, Asep; Suroso, Suroso; anggela, Flora Patricia (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2022)
This study aims to analyze the influence of leadership and work culture on employee performance. In this study, samples taken as many as 124 people. Methods of data analysis using path analysis. The results of the descriptive analysis of the leadership of PT Densha Indoguna Jaya Indonesia have a score of 5650 with an average value of 470.83 and are in the agreed criteria, work culture has a score of 5284 with an average score of 440.3 and are on the agreed criteria, employee performance has a score of 5353 with the average score was 446.1 and was in the agreed criteria The results of the correlation analysis test (r) between leadership (X1) and Work Culture (X2) amounted to 0.506. This shows the relationship between the variables of Leadership to Work Culture is quite strong and positive. The results of the linear regression test partially the influence of Leadership (X1) and Work Culture (X2) on Employee Performance, the partial influence for leadership (X1) on employee performance (Y) amounted to 10.89%, while the partial influence for work culture (X2) on employee performance (Y) of 16.56%. The results of the simultaneous influence of Leadership and Work Culture on Employee Performance are 41.0%, while the remaining 59% of employee performance is influenced by other variables.